Visual Storytelling as Resistance. Reimagining migrant identities through participatory photodocumentation - Elisa Robbe; Alexandra Sanchez; July De Wilde (Obra Digital)
This article explores the Right to Grow Old (RTGO), a participatory photo-documentary that captures Honduran migration through visual self-representation and counter-documentation. Applying Multimodal Positive Discourse Analysis (MPDA), the study examines how RTGO uses personalization, universalization, and deconstruction to shift common portrayals of migrants as anonymous or passive victims. The findings highlight how photo-documentation acts as a form of self-translation, enabling migrants to express complex identities that resist reductive stereotypes. Through a blend of visual and textual narratives, RTGO offers a more nuanced perspective on migration, fostering an ‘oppositional gaze’ that opens new avenues for migrant agency within digital spaces.